Global Value Chain: An Analysis of Pakistan's Textile Sector. Issue 4 (August 2021) - Javed, Ayesha; Atif, Rao Muhammad
Global value chains (GVCs) dominate international production, world trade and investment flows today. This study examines the international fragmentation of production set by GVCs in the textile sector of Pakistan. The study quantifies the data at two- and four-digit level of harmonized code and compares it with top 15 textile exporters around the globe. The estimates through revealed comparative advantage indicate that Pakistan has a competitive edge in cotton and textile made-ups. This indicates that Pakistan needs to bring structural changes by diversifying its product range, reforming tariff procedures, improving working conditions, developing skills and developing cluster in order to promote its exports in GVCs.